Recent Advances in Antimicrobial Nanodrugs - Wu, Fu-Gen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a collection of studies on antimicrobial nanodrugs; it includes four review papers on anti-biofilm therapy, carbon dot-based antimicrobial materials, and supramolecular assemblies for combating antibiotic resistance, as well as six research papers on antibiotic-loaded mesoporous silica nanoparticles, mesostructured spherical nanoparticles, silver nanoparticles, perfluorocarbon nanoemulsion, nano-polyoxometalates, and gold nanoprisms.